2004
DOI: 10.1126/science.1096202
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Dendritic Protein Synthesis by Miniature Synaptic Events

Abstract: Methods Cell Culture and MicroscopyDissociated postnatal (P1-2) rat hippocampal neuron cultures, plated at a density of 230-460/ mm 2 , were prepared as previously described (1). In all experiments, neurons were used following 14-23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
207
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(222 citation statements)
references
References 29 publications
(4 reference statements)
13
207
1
1
Order By: Relevance
“…Scaling in those cases has additional similarities to intermediate-and long-term facilitation: Both types of plasticity can involve postsynaptic Ca 2+ (8,23,33), protein synthesis (8,23,34), AMPA receptor insertion (7,8,16,33), and modulation of the presynaptic probability of release (10)(11)(12)15). However, scaling has an opposite sign of action compared with facilitation (during scaling, spontaneous release acts to decrease protein synthesis and synaptic strength).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaling in those cases has additional similarities to intermediate-and long-term facilitation: Both types of plasticity can involve postsynaptic Ca 2+ (8,23,33), protein synthesis (8,23,34), AMPA receptor insertion (7,8,16,33), and modulation of the presynaptic probability of release (10)(11)(12)15). However, scaling has an opposite sign of action compared with facilitation (during scaling, spontaneous release acts to decrease protein synthesis and synaptic strength).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that spontaneous release also contributes to several other synaptic effects, including some cases of homeostatic scaling (7)(8)(9)(10)(11)(12)(13)(14). Scaling in those cases has additional similarities to intermediate-and long-term facilitation: Both types of plasticity can involve postsynaptic Ca 2+ (8,23,33), protein synthesis (8,23,34), AMPA receptor insertion (7,8,16,33), and modulation of the presynaptic probability of release (10)(11)(12)15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these cells are considered to have an unusually large cytoplasmic volume or storage function. It is well known, however, that localized protein synthesis is critical for synaptic plasticity and maintenance (Sutton and Schuman, 2005;Sutton et al, 2004;Wiersma-Meems et al, 2005). Furthermore, neuronal signal transmission may require a high level of protein synthesis; however, a requirement for more ribosomes per se does not completely explain the life-long sustained high level of pre-rRNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Schuman and colleagues created a dendritic translation reporter by flanking the coding sequence for GFP with the 5 0 and 3 0 untranslated regions (UTR) of the a subunit of Ca 2þ /calmodulindependent kinase II (aCaMKII) (Fig. 3A.1) (Aakalu et al 2001;Sutton et al 2004). The 3 0 UTR of aCaMKII has been shown to be sufficient for dendritic localization of the mRNA in neurons.…”
Section: Fluorescent Protein Reportersmentioning
confidence: 99%